Koinonia (deelgenootskap): 'n gemis in ons 21ste eeuse kerkbegrip - De Wet, B. W. (Faculty of Theology, University of the Free State, 2008)
English: This article argues that in translating koinonia one should not use terms such as “fellowship”, as koinonia focuses on the idea of “sharing”, in particular within a dynamic relationship of active participation and shared interests. After showing how Paul succeeds in applying the koinonia dynamics when addressing some of the issues of the Corinthian church in, for instance, 1 Corinthians 8:1-11:1, it becomes clear that one should rather attempt to make koinonia part and parcel of our current church concept.
Keywords: Pauline literature; Koinonia; Partnership; Letters to the Corinthians; Paul